ANALISIS SUMBER DAN PENGGUNAAN KAS PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA SAMARINDA - Siti Muayyanah; Set Asmapane; Ibnu Abni Lahaya (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
SITI MUAYYANAH. Analysis of Sources and Cash Usage in Institutions Amil Zakat National (BAZNAS) City of Samarinda under guidance of Mr. Set Asmapane and Mr. Ibnu Abni Lahaya.This study aims to find a change in cash by knowing what the source and use of cash in the Institutions Amil Zakat National (BAZNAS) City of Samarinda. The method used in this research is comparative descriptive analysis to determine the existence of cash change through the comparison financial statement between two consecutive years. The technique of data collection that used is by conducting field studies that include observation, interview, documentation and literature study.The results of this study indicate that the analysis of sources and use of cash on Badan Amil Zakat Nasional (BAZNAS) Samarinda city in 2014 and 2015 it can be said that he use of cash made by the Badan Amil Zakat Nasional Samarinda City is less precise, because of the need for infaq/alms funds filled by zakat funds, this is caused by not optimal collection source of infaq/shodaqoh funds in 2015 which impacts on the unaffordable use of infaq/alms funds and cultivate the use of zakat the use of zakat funds to cover the budget shortage use of the infak funds/alms. Whereas according to PSAK 109 are classification zakat funds and infak/alms funds mush be separated should not be mixed, because in terms of acceptance or use there is an allocation of each.